Fermentasi Tumpi Jagung Dengan Bioaktivator yang Berbeda Terhadap Kandungan Serat Kasar Acid Detergent Fiber dan Neutral Detergent Fiber - Annisa Permatasari; Sri Sukaryani (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
Corn cob waste (tumpi jagung) has potential as a livestock feed due to its abundant availability; however, it is characterized by low crude protein content and high crude fiber content, which limits its utilization. Therefore, efforts are needed to reduce its crude fiber content to improve its nutritional value for livestock. This study aimed to evaluate the effect of corn cob fermentation using MA-11 and EM-4 bioactivators on crude fiber (CF), acid detergent fiber (ADF), and neutral detergent fiber (NDF) contents. The study was conducted in February 2025 at the Laboratory of the Faculty of Agriculture, Univet Bantara. The experimental design used was a Completely Randomized Design (CRD) with a one-way pattern, consisting of three treatments and eight replications. The treatments were as follows : 250 g corn cob + 2 g urea + 5 cc molasses; 250 g corn cob + 5 cc MA-11 + 2 g urea + 5 cc molasses; 250 g corn cob + 5 cc EM-4 + 2 g urea + 5 cc molasses. All treatments were incubated for 7 days. The observed variables were crude fiber (CF), ADF, and NDF contents. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). The results showed that fermentation of corn cob waste using MA-11 and EM-4 significantly reduced crude fiber, ADF, and NDF contents. Unfermented corn cob contained CF 6.36%, ADF 39.64%, and NDF 50.59%. Fermentation with MA-11 resulted in CF 4.33%, ADF 33.96%, and NDF 48.33%, whereas fermentation using EM-4 produced CF 3.70%, ADF 32.88%, and NDF 46.78%. The EM-4 bioactivator was more effective in reducing fiber components, with decreases of 0.63% in crude fiber, 1.08% in ADF, and 1.55% in NDF compared to MA-11.